2006
DOI: 10.1038/sj.jcbfm.9600253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Mild Hypothermia or Short-Term Mild Hypothermia on Outcome of Patients with Severe Traumatic Brain Injury

Abstract: To compare the effect of long-term mild hypothermia versus short-term mild hypothermia on the outcome of 215 severe traumatic brain injured patients with cerebral contusion and intracranial hypertension. At three medical centers, 215 patients aged 18 to 45 years old with an admission Glasgow Coma Scale <-8 within 4 h after injury were randomly divided into two groups: long-term mild hypothermia group (n = 108) for 5 +-1.3 days mild hypothermia therapy and short-term mild hypothermia group (n = 107) for 2 +-0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(114 citation statements)
references
References 41 publications
2
108
0
4
Order By: Relevance
“…c Significant differences compared with the values in groups 1, 4, and 5 at same time point (P < 0.001). premise is partially supported by the clinical studies of Jiang et al (2006) who have showed the benefits of more prolonged (4 to 5 days) hypothermic intervention, a strategy whose benefits may, in part, be related to the attenuation of the damaging consequences of secondary insults described above.…”
Section: Discussionmentioning
confidence: 91%
“…c Significant differences compared with the values in groups 1, 4, and 5 at same time point (P < 0.001). premise is partially supported by the clinical studies of Jiang et al (2006) who have showed the benefits of more prolonged (4 to 5 days) hypothermic intervention, a strategy whose benefits may, in part, be related to the attenuation of the damaging consequences of secondary insults described above.…”
Section: Discussionmentioning
confidence: 91%
“…In a comparison of a longer course of mild hypothermia (33-35°C for 3-14 days) with normothermia, mortality was found to be lower and 1-year GOS scores were better for the hypothermia group 62 . A subsequent study that compared short-term (1-3 days) and longterm (4-6 days) mild hypothermia found that patients given a course of hypothermia for 5 days had significantly better 6-month GOS scores than those given a 2-day course 63 . Finally, patients who received systemic cooling (full body) were compared with those who received selective brain cooling (head only) and normothermia.…”
Section: Chinamentioning
confidence: 99%
“…This is important, for example, because of various trials conducted in mainland China that have shown beneficial effects of decompressive craniectomy, hypothermia, and progesterone. 10,[12][13][14][15] These were all well-designed, high-quality studies. However, it is conceivable that differences may exist in referral policies, potential for selection bias, access to health care, acute and post-acute treatments, and outcome.…”
Section: Clinical Trials In Tbi: Past Experiencementioning
confidence: 99%